1975
DOI: 10.1085/jgp.66.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Routes of nonelectrolyte permeability in gallbladder. Effects of 2,4,6-triaminopyrimidinium (TAP).

Abstract: The organic cation 2,4,6-triaminopyrimidinium (TAP), which blocks the tight junction channels for cation permeability across gallbladder, also inhibits gallbladder permeability (P) to urea and glycerol without significantly affecting P to Cl-, sucrose, 1,7-heptanediol, or water (osmotic or diffusional permeabilities). These effects together with the comparisons of P's in frog with P's in rabbit gallbladder suggest that sucrose migrates exclusively through the leakage pathway (through where C1-permeates), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…TAP had no effect on either PEG permeability or absorptive water flux (Table1); this observation neither supports nor opposes our conclusions, but this lack of effect is by no means unprecedented. For example, in rabbit and frog gall bladder preparations, where there was strong evidence for paracellular permeability to several small molecules, TAP did not affect net water or Cl -flux rates, or the permeability to sucrose, a molecule of comparable size to PEG-400 (Moreno, 1975). The author concluded that water was permeating mainly via the transcellular route.…”
Section: Discussion Overviewmentioning
confidence: 99%
“…TAP had no effect on either PEG permeability or absorptive water flux (Table1); this observation neither supports nor opposes our conclusions, but this lack of effect is by no means unprecedented. For example, in rabbit and frog gall bladder preparations, where there was strong evidence for paracellular permeability to several small molecules, TAP did not affect net water or Cl -flux rates, or the permeability to sucrose, a molecule of comparable size to PEG-400 (Moreno, 1975). The author concluded that water was permeating mainly via the transcellular route.…”
Section: Discussion Overviewmentioning
confidence: 99%
“…Previous work, however, suggests that the situation is quite different in the rabbit gall-bladder. In that epithelium, although a significant sucrose permeability is evident in the absence of fluid transport (1-8 x 10-6 cm sec', Moreno, 1975b), relatively little sucrose appears in the absorbate during fluid transport (Diamond, 1964b).…”
Section: Discussionmentioning
confidence: 99%
“…The second of these three routes was attributed initially to a polar pathway through the epithelial cell membranes (Wright & Diamond, 1969). More recently though, Moreno (1975b) has demonstrated that 2,4,6-triaminopyrimidinium (TAP), which blocks the paracellular cation channels, also reduces the permeability to small polar non-electrolytes, so there may in addition, or alternatively, be a substantial paracellular permeability to these smaller molecules.…”
Section: Discussionmentioning
confidence: 99%
“…No direct or reliable method to approach this question exists at present. Some authors cite indirect evidence to support a predominantly transcellular route for leaky epithelia (e.g., Wright etal., 1972;van Os & Slegers, 1973;Moreno, 1975;van Os et al, 1979). Other authors cite indirect evidence to support a predominantly transjunctional route (e.g., Sackin & Boulpaep, 1975;Fischbarg et al, 1977;Hill & Hill, 1978a and b).…”
Section: Transeellular Vs Transjunctional Route Of Water Flowmentioning
confidence: 99%